ANALISIS YURIDIS TERHADAP TINDAK PIDANA YANG DILAKUKAN OLEH PENYEDIA APLIKASI PINJAMAN ONLINE - Dirga Agung, Wahyu Rasyid (FAKULTAS HUKUM UM PAREPARE, 2021)
Since This research discusses the types of crimes committed by online loan application providers and criminal sanctions against criminal acts committed by online loan application providers. In addition, this study examines criminal acts related to interference (interference) within the scope of online loan applications. The results of this study refer to Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions, Government Regulation of the Republic of Indonesia Number 82 of 2012 concerning Implementation of Electronic Systems and Transactions, and Regulation of the Minister of Communication and Information of the Republic of Indonesia. Indonesia Number 7 of 2016 concerning Administration of Investigation and Enforcement of Criminal Acts in the Field of Information Technology and Electronic Transactions. Then legal protection for online loan application users occurs when the obligations of the online loan application provider are not carried out, it can be resolved through litigation (courts) or non-litigation channels (mediation, reconciliation, etc.).